Prevalence and Risk Factors of Myopia in Young Adults: Review of Findings From the Raine Study - Lee, Samantha Sze-Yee; Mackey, David A. (Frontiers in Public Health, 2022)
Myopia tends to develop and progress fastest during childhood, and the age of stabilisaton has been reported to be 15–16 years old. Thus, most studies on myopia have centred on children. Data on the refractive error profile in young adulthood — a time in life when myopia is thought to have stabilised and refractive error is unaffected by age-related pathology such as cataract — are limited. The Raine Study has been following a community-based cohort of young adults representative of the general Western Australia population since their prenatal periods in 1989–1991 and has documented the prevalence of refractive errors, along with the profile of a myriad of other ocular measures. At 20 years old, prevalence of myopia in the cohort were 25.8%. Using serum vitamin D levels and conjunctival ultraviolet autofluorescence (CUVAF) area to quantify sun exposure, the Raine Study confirmed an inverse relationship between time spent outdoors and myopia prevalence. Several novel potential associations of myopia or ocular biometry were investigated, including foetal growth trajectory, which was found to be significantly associated with corneal curvature at 20 years. By age 28, myopia prevalence had increased to 33.2%, respectively. Smaller CUVAF area at follow-up, female sex and parental myopia were significant risk factor for myopia incidence and progression between 20 and 28 years. Given the limited research in young adults, further investigations are warranted to confirm the Raine Study findings, as well as identify novel genetic or environmental factors of myopia incidence and progression in this age group.